2018
DOI: 10.1002/ajh.25349
|View full text |Cite
|
Sign up to set email alerts
|

The germline JAK2 GGCC (46/1) haplotype and survival among 414 molecularly‐annotated patients with primary myelofibrosis

Abstract: JAK2 mutations in myeloproliferative neoplasms (MPNs) are associated with the germline GGCC (46/1) haplotype. In 2010, we reported an association between shortened survival in primary myelofibrosis (PMF) and nullizygosity for the JAK2 46/1 haplotype. In the current study, we have increased the number of informative cases from 130 to 414 (median age 63 years; 63% males), in order to revisit with the phenotypic and prognostic relevance of the JAK2 46/1 haplotype in PMF. JAK2 46/1 haplotype was documented in 69% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…According to the WHO classification, the PMF cohort includes prefibrotic myelofibrosis and overt myelofibrosis. We show that PMF subjects with the rs3025039 minor T-allele have an increased susceptibility to the JAK2 V617F driver mutation, in keeping with data indicating that other genetic polymorphisms in JAK2, MECOM, TERT, TET2, HBS1L-MYB, and the corticosteroid receptor predispose to acquiring JAK2 V617F [26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…According to the WHO classification, the PMF cohort includes prefibrotic myelofibrosis and overt myelofibrosis. We show that PMF subjects with the rs3025039 minor T-allele have an increased susceptibility to the JAK2 V617F driver mutation, in keeping with data indicating that other genetic polymorphisms in JAK2, MECOM, TERT, TET2, HBS1L-MYB, and the corticosteroid receptor predispose to acquiring JAK2 V617F [26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…In a first study published in 2010, nullizygosity for the JAK2 haplotype was associated to shortened survival in a cohort of 130 PMF patients [55]. Subsequently, in a follow-up study on a cohort of 414 molecularly annotated PMF, the authors confirmed that wild-type patients displayed inferior overall survival as compared to the other genotypes, independently from well-established genetic and cytogenetic markers of poor outcome (karyotype, driver mutational status, presence of high-molecular-risk mutations) [56].…”
Section: Host Genetic Variants Modulating Disease Phenotype And/or Outcomementioning
confidence: 88%
“…Host genetic variants such as single nucleotide polymorphisms (SNPs) are emerging as important players in modulating the individual pro-inflammatory background by affecting cytokine/chemokine gene expression and mRNA levels [ 8 ]. Indeed, inherited genetic variants predisposing to MF onset, phenotype and outcome, such as the JAK2 GGCC_46/1 haplotype [ 9 , 10 ] and the rs6198 SNP of NR3C1 [ 11 ], have also the potential to predispose to enhanced inflammatory state and autoimmune disorders [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%